Nikos Skalkottas and Dimitris Dragatakis: Interactions of their lives and creative paths - Kalopana Magdalini (Muzikologija)
Nikos Skalkottas (1904-1949) and Dimitris Dragatakis (1914-2001) were two of the most important Greek composers of the twentieth century. From 1944 to 1947, they both played in the orchestra of the Greek National Opera, Dragatakis being a politically engaged apprentice composer and Skalkottas a marginalized violin virtuoso and avant-garde pioneer. While no direct connection between them is documented, new sources suggest some interaction of their lives and creative paths. Analysis of two pieces for violin and piano - the second movement of Skalkottas’ Sonatina no. 1 (1929), and Lullaby [Berceuse/Nanourisma] [1942-1949] by Dragatakis - indicates Dragatakis’ early adoption of the twelve-tone techniques from Skalkottas’ work, hinting at the initial influence of Skalkottas’ modern procedures in Greece.